Biomarkers of exposure to lead - Gerlach, Raquel Fernanda; Gonçalves, Soraya Cheier Dibb; Guerra, Carolina Souza (Medicina (Ribeirao Preto), 2009)
This article aims at describing some of the most important biomarkers of exposure to lead, showing its advantages and limitations, as well as how they relate to present, past or cumulative exposure to lead. This basic knowledge is essential for the comprehension of the effects of lead, the difficulties of the diagnosis of excessive exposure, and the problem of exposure to low levels of lead. The biomarkers of exposure discussed in depth in this article are blood, bone, and teeth.